Between Rights and Power Asymmetries: Contemporary Struggles for Land in Brazil and Colombia (2013)
The struggles for land discussed in this paper have occurred in contexts characterized by some improvement of laws and policies designed to protect ethnic and cultural minorities in Brazil and Colombia, following the “multicultural turn” in international law. The paper discusses to a greater extent the cases of communities of Afro-descendants who live in areas disputed by agribusiness companies interested in expanding palm plantations mostly for biodiesel production. We found out that the introduction of new rights has first unleashed a local process of ethnic re-identification. In a certain way, minority rights themselves have created those minorities they are supposed to protect. Nevertheless, new minority rights have also reframed the conditions under which struggles for land are conducted and negotiated in Colombia as well as in Brazil. Seen as relays in an electrical circuit, minority rights serve to modulate power at the local level: in some cases, new rights amplify minorities’ power; in other situations, they can help contain the problems of abuses of power.